Intracellular free fatty acid upholds β‐cell glucose competence: The role of peroxisome proliferator‐activated receptor δ and mitochondrial metabolism. Issue 2 (15th July 2014) - Takei, Masahiro; Komatsu, Mitsuhisa; Aizawa, Toru
<x xml:space="preserve">Abstract</x> Tang et al. identified a novel downstream signaling pathway for intracellular FFA in pancreatic beta cells: activation of peroxisome proliferator‐activated receptor δ (PPARδ) followed by enhanced mitochondrial metabolism. This was accomplished by using beta‐cell specific desnutrin/ATGL knockout (desnutrin βKO) mice. <boxed-text content-type="graphic" id="jdi12257-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>